MODERNIZING THE PhD COURSE IN THE NEW SYSTEM OF HIGHER EDUCATION - Svetlana V. Badmaeva; Ekaterina V. Novikova; Evgeniya V. Shubenkova (Вестник Российского экономического университета имени Г. В. Плеханова)
The article deals with changes and amendments introduced in the Federal law ‘About Education in the Russian Federation’ and rules of  enrollment in the PhD course in the aspect of training academic and  pedagogical personnel. The scale of appraising key individual  achievements for enrollment in the PhD course was provided, which  was illustrated by leading universities of Russia in the field of  economics. Figures of participants’ graduation were analyzed by  science sectors in 2015 and 2016, including those with dissertation  defense. Key reasons for the PhD course enrollment were shown and specific features of the PhD course enrollment in overseas countries  were identified. It was proposed to take into account additional  indicators of candidates’ individual achievements, which could give  priority rights to be enrolled in case of equal competitive scores.  Recommendations were put forward aimed at PhD course modernization in the field of dealing with candidates and personnel with high qualification.